Water consumption rate of konkan kanyal goats (Capra hircus) fed finger millet straw supplemented with varying levels of dried poultry dropping based diets - Abdulwaheed Adeyemi Bello; Balakrishna Gunaji Desai; Ramesh Ganu Burte; Vishnu Sakhoram Dandekar; Janarda Shamroa Dhekale; Shalu Kumar; Weldegerima Kide Gebremedhin (Syiah Kuala University, 2016)
This study was conducted to estimate the water intake of konkan kanyal goats fed finger millet straw supplemented with varying levels of dried poultry droppings based diet. Thirty konkan kanyal goats aged above 12 months weighing 14.00-14.67 Kg were used in a randomized block design (RBD) experiment. The experimental goats were randomly assigned to five treatments (TI-T5). T1 were goats fed with 0 % dried poultry droppings based diets (DPDBD), T2 were fed with 20 % dried poultry droppings based diets (DPDBD), T3 were fed with 40 % dried poultry droppings based diets (DPDBD), T4 were fed with 60 % dried poultry droppings based diets (DPDBD), T5 were fed with 80 % dried poultry droppings based diets (DPDBD. Water was offered at 5 L per goats daily. Water and feed refusal were recorded on a daily basis before feeding in the morning. Feed and feaces samples were analyzed for proximate constituents. Live weight changes were also measured. Results revealed that treatment groups supplemented with dried poultry droppings based diets had superior water intake compared to the control group. Daily water intake of the experimental goats was 1.4, 2.2, 3.5, 2.7, and 1.7 L per head, respectively. Konkan kanyal goats fed finger millet straw supplemented with varying levels of dried poultry dropping based diets requires up to 3.5 L of water per head per day for optimum utilization of the feed.